2017
DOI: 10.1017/9781107588196
|View full text |Cite
|
Sign up to set email alerts
|

International Law and World Order

Abstract: In International Law and World Order, B. S. Chimni articulates an integrated Marxist approach to international law (IMAIL), combining the insights of Marxism, socialist feminism, and postcolonial theory. The book uses this approach to systematically and critically examine the most influential contemporary theories of international law, including new, feminist, realist, and policy-oriented approaches. In doing so, it discusses a range of themes relating to the history, structure, and process of international la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(8 citation statements)
references
References 302 publications
0
7
0
1
Order By: Relevance
“…In 2014, Chimni and co-workers reported a peptide-catalyzed, asymmetric ring-opening reaction of meso-stilbene oxides 5.28 with N-phenylpiperazine 5.29 to access chiral amino alcohols 5.30 (Figure 94). 233 The general catalyst design centered on short, β-turn forming sequences capped with an N-terminal thiourea moiety. In that way, the authors intended to capitalize on the demonstrated ability of thioureas to activate electrophiles through Hbonding interactions, 234 as well as the folded secondary structures of peptides to provide a robust chiral environment for asymmetric induction.…”
Section: Meso-epoxide Openingmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2014, Chimni and co-workers reported a peptide-catalyzed, asymmetric ring-opening reaction of meso-stilbene oxides 5.28 with N-phenylpiperazine 5.29 to access chiral amino alcohols 5.30 (Figure 94). 233 The general catalyst design centered on short, β-turn forming sequences capped with an N-terminal thiourea moiety. In that way, the authors intended to capitalize on the demonstrated ability of thioureas to activate electrophiles through Hbonding interactions, 234 as well as the folded secondary structures of peptides to provide a robust chiral environment for asymmetric induction.…”
Section: Meso-epoxide Openingmentioning
confidence: 99%
“…Figure 95.Asymmetric ring-opening of stilbene oxides 5.28 with piperazine 5.29 catalyzed by thiourea-functionalized peptide 5.31a 233. …”
mentioning
confidence: 99%
“…43 Chimni'ye göre egemen eşitlik prensibi ekseninde akdi ilişkilere binaen gelişen uluslararası hukuk, kapitalizmin ve dolayısıyla kendisinin gelişimine katkı koyan sömürgeciliği, 17. yüzyılda Hollanda egemenliğindeki dünya sistemi içerisinde düzenlemeye tabi tutmaya başlamıştır. 44 Müteakip hegemon olan İngiltere; sömürgelerle ticareti kendi denizciliğinin tekeline alıp, kendi ülkesindeki üretimle rekabete girebilecek sömürge üretimini yasaklarken sadece 17. yüzyıl sonunun uluslararası işbölümünü değil, dönemin uluslararası hukukunu da belirlemekteydi. 45 İngilizlerin iktisadi-siyasi eylemleri ekseninde bir yanda hammadde üreticileri, diğer yanda mamul mal üreticilerinin bulunduğu bir dünya ekonomisi yavaş yavaş belirmekteyken, Avrupa içerisinde merkantilist ekonomilerle bağlantı içerisinde mutlakıyetçi devletin ortaya çıkışını da gözlemlemek mümkün hale gelmişti.…”
Section: Eski Ve Yeni Sömürgecilik Dönemleriunclassified
“…7 Chimni, for example, demonstrates how states use the legal doctrine of jurisdiction to naturalise legal categories such as 'nationals' and 'aliens', and to legitimise social injustice and economic inequality. 8 Literature in the intersection of law and technology has further explored the role of technologies and data analytics in importing inequalities to the domain of international law. Analysing smart borders technologies, Van Den Meerssche demonstrates how 'social hierarchies' are 'reproduced by practices of algorithmic association'.…”
Section: Introduction 'Colonel Powell: "If My Targeteer Can Calculate...mentioning
confidence: 99%